Sexually transmitted founder HIV-1 viruses are relatively resistant to Langerhans cell-mediated restriction. - Nina Hertoghs; Bernadien M Nijmeijer; Nienke H van Teijlingen; Angharad E Fenton-May; Tanja M Kaptein; John L van Hamme; John C Kappes; Neeltje A Kootstra; Beatrice H Hahn; Persephone Borrow; Carla M S Ribeiro; Teunis B H Geijtenbeek (PLoS ONE)
A single HIV-1 variant establishes infection of the host after sexual contact. Identifying the phenotypic characteristics of these Transmitted Founder (T/F) viruses is important to understand the restriction mechanisms during transmission. Langerhans cells (LCs) are the mucosal dendritic cell subset that has been shown to have a protective role in HIV-1 transmission. Immature LCs efficiently capture and degrade HIV-1 via langerin-mediated restriction. Here we have investigated the capacity of T/F HIV-1 strains to infect mucosal Langerhans cells (LCs). Notably, most T/F variants efficiently infected immature LCs derived from skin and vaginal tissue in contrast to chronic HIV-1 laboratory strains. Next we screened a panel of T/F viruses and their matched 6-month consensus sequence viruses. Interestingly most T/F variants infected immature LCs whereas donor-matched 6-month consensus sequence viruses had lost the ability to infect LCs. However, we also identified 6-month consensus sequence viruses that had retained an ability to infect LCs similar to that of the donor-matched T/F virus. Moreover, some T/F viruses and 6-month consensus sequence viruses were unable to infect immature LCs. Further analyses indicated that T/F viruses are less sensitive to langerin-mediated restriction. These data suggest that T/F HIV-1 variants have the ability to infect immature LCs, which will facilitate transmission.